ANALISIS MODEL AKTUARIA PADA ASURANSI DISABILITAS INDIVIDU TERINFEKSI HIV/AIDS - Heryka Ade Muspitta (Jurnal Matematika, 2016)
1, Djuwandi2, Sunarsih3 1,2,3Departemen Matematika FSM Universitas DiponegoroJl. Prof. H. Soedarto, S.H. Tembalang Semarang , djuwandi225433@gmail.com ABSTRACT. Actuarial model can be constructed by a multiple state model. Multiple state model is a model that describes a probability of moving random of the individual by investigated states. This model is a multiple state model for the individual infected by HIV/AIDS with states are at risk, HIV Positive, AIDS and dead. To obtain the probability of individual suffering HIV/AIDS used by transition intensity approach. Transition intensities estimated by parameter estimation method is Maximum Likelihood. To set of the transition probabilities from parameter estimation can be derived by Kolmogorov forward diferential equation. This transition probabilities to determine pricing of actuarial present value of disability insurance product. Numerical simulation is giving lower actuarial present value for female than male with ratio 1,03 % in the Balai Kesehatan Paru Masyarakat Wilayah Semarang. Keywords: